Elbow and wrist joint loading during the round-off skills in male gymnastics: A case study - Farana, R.; Janeczkova, P.; Uchytil, J.; Jandacka, D.; Zahradnik, D.; Irwin, G. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Elbow and wrist injuries are a major concern in elite male gymnastics. The aim of the current study was to investigate key elbow and wrist joint injury risk factors (internal and external kinetics) during different round-off techniques in male artistic gymnastics. One international level male gymnast performed 15 trials of a round-off from a hurdle step to back handspring with three different hand positions (parallel (5), T-shape (5) and reverse (5)). Synchronized kinematic and kinetic data were collected for each trial. Effect-size statistics determined differences between each hand position. In conclusion the T-shape technique demonstrated reduced vertical, anterior-posterior and resultant ground reaction forces. Differences in elbow and wrist joint kinetics indicated that the T-shape technique may prevent elbow and wrist joint from overload and reduces potential of injuries.